Synthetic biology: the many facets of T7 RNA polymerase. Issue 7 (July 2014) - Shis, David L; Bennett, Matthew R
<x xml:space="preserve">Abstract</x> Split T7 RNA polymerase provides new avenues for creating synthetic gene circuits that are decoupled from host regulatory processes—but how many times can this enzyme be split, yet retain function? New research by Voigt and colleagues (Segall‐Shapiro et al, 2014) indicates that it may be more than you think.